Ethnicity, culture and indigenous leadership in modern politics: the case of the Kadazandusun In Sabah, East Malaysia - Puyok, Arnold; Bagang, Tony Paridi (2011)
The main purpose of the study was to examine the role of ethnic identity, culture and indigenous leadership institution in shaping the political change of the Kadazandusun. Drawing from the framework of ethnic factor in Malaysia's politics, the examination of the three inter-related issues was complemented by a survey conducted among 200 Kadazandusun in Penampang, Ranau and Tambunan. The findings suggest that ethnic identity remains a crucial component in the political change of the Kadazandusun. The Kadazandusun political elites not only use the identity issue as a "bargaining tool’, they also use it to raise ethnic sentiment to win popular support. A majority of the Kadazandusun surveyed in the study believed that the identity issue has been used for political mileage and that is it time for the Kadazandusun leaders to solve the issue once and for all. All the Kadazandusun-based cultural associations remain an important "grassroots base" for the Kadazandusun political elites. The respondents believed that the Kadazandusun political leaders are not united and should be blamed for causing the Kadazandusun to split. Joseph Pairin Kitingan is still seen as the prominent figure who is capable of uniting the Kadazandusun. Even though his status as Huguan Siou is relevant to some Kadazandusun, some of the respondents wanted Pairin not to use his Huguan Siou title for political expediency and would prefer the indigenous leadership institution to remain "traditional".